2021
DOI: 10.1063/5.0059690
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of crown-motif [Au9(PPh3)8]3+ and [MAu8(PPh3)8]2+ (M = Pd, Pt) clusters: Effects of gas composition, single-atom doping, and counter anions

Abstract: The thermal behaviors of ligand-protected metal clusters, [Au9(PPh3)8]3+ and [MAu8(PPh3)8]2+ (M = Pd, Pt) with a crown-motif structure, were investigated to determine the effects of the gas composition, single-atom doping, and counter anions on the thermal stability of these clusters. We successfully synthesized crown-motif [PdAu8(PPh3)8][HPMo12O40] (PdAu8–PMo12) and [PtAu8(PPh3)8][HPMo12O40] (PtAu8–PMo12) salts with a cesium-chloride-type structure, which is the same as the [Au9(PPh3)8][PMo12O40] (Au9–PMo12) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…1 and Supplementary Fig. S 1 showed the characteristic optical properties of crown-motif Au9-C, PdAu8-C and PtAu8-C , respectively 34 . ESI-MS and NMR spectra in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…1 and Supplementary Fig. S 1 showed the characteristic optical properties of crown-motif Au9-C, PdAu8-C and PtAu8-C , respectively 34 . ESI-MS and NMR spectra in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…In the case of non-doped [Au 9 (PPh 3 ) 8 ] 3+ , butterfly-motif Au9-B was formed in Au9-NO3 composite, which was formed from Au9-C ethanol solution by isomerization 32 . DR-UV-Vis-NIR spectrum of Au9-NO3 with a butterfly-motif structure showed a characteristic absorption peak at 687 nm, which differed from those of Au9-C solution ( Au9-NO3 in ethanol) and crown-motif [Au 9 (PPh 3 ) 8 ][PMo 12 O 40 ] ( Au9-PMo12 ) 34 . Since the optical property of [Au 9 (PPh 3 ) 8 ][Mo 6 O 19 ] composite ( Au9-Mo6 ) was in accordance with that of Au9-NO3 composite as shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13−15 This isomerization was suppressed in [PdAu 8 (PPh 3 ) 8 ] 2+ (PdAu8, Scheme 1); previous EXAFS studies have shown that the radial Pd−Au and lateral Au−Au bonds in PdAu8 are both stiffer than the corresponding Au− Au bonds in [Au 9 (PPh 3 ) 8 ] 3+ . 13 Rigidification of the Au−Au bonds in Au9 by Pd atom doping (PdAu8) leads to the enhanced thermal stability 16 and catalytic activity after ligand removal. 17 In this study, we investigate how the fluxionality of superatomic cores affects the collision-induced dissociation (CID) pathway.…”
mentioning
confidence: 99%
“…The desorption of L′ from Au9′ was more endothermic (1.22 eV, Figure 3) than that from PdAu8′ (0.75 eV, Figure 2). 16 These energetic considerations explain the occurrence of reaction 3 under low V i conditions without dissociation of the ligand (Figure 1f). The difference of preferable dissociation routes between PdAu8′ and Au9′, in particular at small collision energy (CE exp = 0.18 eV), could be partly rationalized by net atomic charge analyses (Figures 2 and 3).…”
mentioning
confidence: 99%